A system of pleas: social science's contributions to the real legal system - Edkins, Vanessa A.; Redlich, Allison D. (American psychology-law society series, 2019)
Introduction:A system of pleas /Vanessa A. Edkins and Allison D. Redlich --Section 1.The system of pleas and its players --Arriving at a system of pleas : the history and state of plea bargaining /Lucian E. Dervan --Defendant decision-making in plea bargains /Shawn D. Bushway --Defense attorneys and plea bargains /Kelsey S. Henderson --Prosecutors and plea bargains /Bryan C. McCannon --Section 2.Influences on plea decision-making --Race and plea bargaining /Brian D. Johnson and Rebecca Richardson --Juvenile justice and plea bargaining /Allison D. Redlich, Tina Zottoli, and Tarika Daftary-Kapur --Innocence and plea bargaining /Miko M. Wilford and Annmarie Khairalla --Section 3.Results of a system of pleas --Sentencing disparity and mass incarceration /Rhys Hester --Collateral consequences and disenfranchisement /Vanessa A. Edkins --Conclusion:Moving forward in a system of pleas / Allison D. Redlich and Vanessa A. Edkins.